(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
India has witnessed a paradigm shift in its corporate governance framework, catalyzed by regulatory reforms aimed at fortifying investor confidence and enhancing corporate accountability in recent years. This paper embarks on a comprehensive exploration of these reforms, delving into their multifaceted impact on the Indian business landscape. By meticulously analyzing legislative amendments, corporate behaviors, and empirical evidence, this study assesses the efficacy of these measures in fostering transparency, integrity, and sustainable practices within Indian corporations. Through the lens of case studies and diverse stakeholder perspectives, this research offers nuanced insights into the evolution, strengths, and challenges of corporate governance reforms in India. Furthermore, it illuminates potential pathways for future enhancements, underscoring the imperative for continued vigilance and innovation in navigating the complexities of governance in India's dynamic economic milieu.